The association between intergenerational support and depressive symptoms in older adults: a chain mediation analysis of life satisfaction and well-being - Feng, Wenjia; Geng, Pengxin; Wang, Yan; An, Hongqing; Gao, Qianqian; Cai, Weiqin; Jing, Qi; Gao, Runguo; Ma, Anning (Frontiers in Public Health, 2025)
BackgroundWith the acceleration of population aging, increasing attention has been directed toward mental health issues in later life. Among these, depressive symptoms represent one of the most prevalent psychological concerns and have been consistently associated with lower quality of life and impaired social functioning in older adults. As a primary source of social support for older adults, intergenerational support plays a crucial role in shaping their psychological well-being. This study aims to examine the potential mediating mechanisms linking intergenerational support to depressive symptoms among older adults, within the context of China's traditional culture of filial piety. The findings are intended to provide a theoretical basis for optimizing intergenerational support strategies and promoting mental health in later life.MethodsThis study employed data from the 2020 wave of the China Family Panel Studies (CFPS), focusing on variables related to intergenerational support from children, life satisfaction, well-being, and depressive symptoms. Analysis methods included analysis of variance (ANOVA), Pearson correlation analysis, and bootstrap procedures to examine the chain mediation effects involving intergenerational support, life satisfaction, well-being, and depressive symptoms.ResultsEmotional support (β = −0.431, P ≤ 0.001), life satisfaction (βemotional support = −0.727, P ≤ 0.001; βeconomic support = −0.757, P ≤ 0.001; βcare support = −0.756, P ≤ 0.001), and well-being (βemotional support = −0.468, P ≤ 0.001; βeconomic support = −0.518, P ≤ 0.001; βcare support = −0.504, P ≤ 0.001) were significantly associated with lower levels of depressive symptoms. Economic support (β =0.956, P ≤ 0.001) and care support (β =0.433, P ≤ 0.001) were positively associated with higher levels of depressive symptoms. Life satisfaction and well-being were found to exert a chain mediating effect in the association between intergenerational support and depressive symptoms [emotional support: total effect = −0.825, 95% CI (−0.990, −0.662); direct effect = −0.431, 95% CI (−0.5896, −0.2713); indirect effect = −0.0710, 95% CI (−0.0935, −0.0506); economic support: total effect = 0.7138, 95% CI (0.4609, 0.9667); direct effect = 0.9560, 95% CI (0.7185, 1.1936); indirect effect = −0.0373, 95% CI (−0.0664, −0.0106); care support: total effect = 0.2719, 95% CI (0.0061, 0.5377); direct effect = 0.4334, 95% CI (0.1836, 0.6832); indirect effect = −0.0289, 95% CI (−0.0587, −0.0016)].ConclusionThe findings reveal a chain mediation effect involving life satisfaction and well-being in the association between intergenerational support and depressive symptoms among older adults. Emotional support is positively associated with higher life satisfaction and greater well-being, which in turn are linked to lower levels of depressive symptoms. In contrast, life satisfaction and well-being appear to suppress the positive associations between economic support or care support and depressive symptoms. These results enhance our understanding of the psychosocial pathways through which intergenerational support is related to mental health in later life and provide empirical evidence to inform the design of targeted psychological interventions and social support policies.